Neuron-Material Nanointerfaces: Surface Nanotopography Governs Neuronal Differentiation and Development - Kim, Hoon Kee; Kim, Eunha; Jang, Hongje; Kim, Young-Kwan; Kang, Kyungtae (WILEY-V C H VERLAG GMBH, 2017)
This review summarizes recent experimental results regarding the influences of surface nanotopography on stem cell differentiation into neurons and neuronal development. Collections of observations and their interpretations are provided. We specifically focus on the in vivo implications of the results, by suggesting that: (i) neural cells use their intracellular machineries to actively recognize surface nanotopography; (ii) the preferential differentiation of stem cells into neurons and the developmental acceleration of neurons occur on a range of similar nanotopographical features, implying that they have similar biological backgrounds; and (iii) surface nanotopography, therefore, is deeply involved in brain development. We believe that this review will provide biological insights to the field of nanoneuron interfaces and encourage interdisciplinary efforts capable of addressing unsolved biological problems and increasing engineering needs.
Keywords: EMBRYONIC STEM-CELLS; FOCAL ADHESION KINASE; NERVE GROWTH-FACTOR; NEURITE OUTGROWTH; EXTRACELLULAR-MATRIX; HIPPOCAMPAL-NEURONS; SILICON NANOWIRES; CONTACT GUIDANCE; IN-VITRO; TOPOGRAPHY